2009
DOI: 10.1136/ip.2008.020446
|View full text |Cite
|
Sign up to set email alerts
|

Are school zones effective? An examination of motor vehicle versus child pedestrian crashes near schools

Abstract: Focusing interventions around schools with attention to age, travel times, and crossing location will reduce the burden of injury in children. Future studies that take into account traffic and pedestrian volume surrounding schools would be useful for prevention efforts as well as for promotion of walking. These results will help identify priorities and emphasise the importance of considering spatial and temporal patterns in child pedestrian research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 31 publications
3
46
1
2
Order By: Relevance
“…These characteristics are similar to those found in other studies prior (DiMaggio and Durkin, 2002 [ ( F i g . _ 2 ) T D $ F I G ] Nance et al, 2004;Warsh et al, 2009;Weiner and Tepas, 2009). As other studies have shown, our data also found that injuries were more severe at midblock locations for both child and adult pedestrians (Slaughter et al, 2014;Rothman et al, 2012).…”
Section: Crash Characteristics Compared To Prior Studiessupporting
confidence: 84%
“…These characteristics are similar to those found in other studies prior (DiMaggio and Durkin, 2002 [ ( F i g . _ 2 ) T D $ F I G ] Nance et al, 2004;Warsh et al, 2009;Weiner and Tepas, 2009). As other studies have shown, our data also found that injuries were more severe at midblock locations for both child and adult pedestrians (Slaughter et al, 2014;Rothman et al, 2012).…”
Section: Crash Characteristics Compared To Prior Studiessupporting
confidence: 84%
“…In Germany, traveling to and from school is considered to be part of school attendance, so accidents on the way to school are covered by statutory accident insurance regulations. The fact that the number of traffic accidents increases during school periods compared to during vacations shows that traveling to and from school represents a considerable risk [23,24]. We found no differences in the injuries incurred on the way to school and on the way back home.…”
Section: Discussioncontrasting
confidence: 37%
“…Walking to school was negatively correlated with parents' perceptions of high traffic danger along the school route in this study; however, there was no association between walking and parents' perceptions of high traffic danger at the school site despite reported evidence in previous studies of stop sign violations, dangerous speeding (Taft et al, 2000;Cody and Hanley, 2013;Anderson et al, 2002), and increased density of child pedestrian collisions within 150 m of a school in Toronto (Warsh et al, 2009). A key finding here is that the location of perceived safety-risks matters, and that it is the school route context rather than the school site where parents appear to focus their attention with regard to incorporating traffic safety into the school travel decision.…”
Section: Discussionmentioning
(Expert classified)